Physical Activity Levels in a Community Lifestyle Intervention: A Randomized Trial. Issue 5 (1st June 2016) - Eaglehouse, Yvonne L.; Rockette-Wagner, Bonny J.; Kramer, Mary Kaye; Arena, Vincent C.; Miller, Rachel G.; Vanderwood, Karl K.; Kriska, Andrea M.
Abstract : ABSTRACT: A behavioral lifestyle intervention program with goals of increasing physical activity (PA) and losing weight was shown to be efficacious in preventing type 2 diabetes and decreasing risk of cardiovascular disease (CVD) in the US Diabetes Prevention Program (DPP). Modified versions of the DPP lifestyle intervention are being translated into diverse community settings and have been successful in decreasing weight and improving metabolic markers. However, comprehensive evaluations of PA levels within these community translation intervention efforts are rare. The purpose of this study is to evaluate the effectiveness of a DPP-based community lifestyle intervention for improving PA levels. Two hundred twenty-three overweight adults at risk for type 2 diabetes and/or CVD were randomized (immediate or 6-month delayed-start group) to a 12-month DPP-based lifestyle intervention. The past month's PA level was assessed at baseline and postintervention with the Modifiable Activity Questionnaire. Simple and mixed-effects regression models were used to determine changes in the PA level between and within groups over time. The between-group mean difference for change in PA levels from baseline to 6 months indicated significantly greater improvement in the intervention compared with the delayed-start group (+6.72 MET·h·wk −1 (SE = 3.01), P = 0.03). Examining combined within-group change from baseline to postintervention, we found that mean PA levels significantly increased by +14.69 MET·h·wk −1 (SE = 1.43) and +9.50 MET·h·wk −1 (SE = 1.40) at 6 and 12 months postintervention, respectively. This PA change offset to approximately +10 MET·h·wk −1 at both 6 and 12 months after adjusting for the baseline PA level and season (all, P < 0.01). Other than the season, sex impacted on change in the PA level. In conclusion, this community-based lifestyle intervention significantly increased PA levels among overweight adults at risk for type 2 diabetes and CVD, even after adjusting for key variables.